KAJIAN FILOLOGI DAN NILAI PENDIDIKAN SOSIAL DALAM NASKAH “NGREWANGI APA NGRUSUHI” - Ubaydillah Faqih; Ida Sukowati (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the physical condition and textual content of the manuscript "Ngrewangi Apa Ngrusuhi" and to identify the embedded values of social education. The manuscript, part of the Ranggawarsita Museum collection in Semarang, is written in Javanese script and modern Javanese language. This study employed a descriptive method combined with a philological approach, including inventory, description, transliteration, translation, and content analysis. The findings show that the manuscript is well-preserved with legible writing. The identified values of social education include: (1) compassion (helpfulness, kinship), (2) life harmony (honesty, sharing), and (3) responsibility (discipline, diligence). These findings contribute to the preservation of local culture and support the integration of character education in school curricula.